The employment of the saviour concept in literature: Iraqi novelist production post-war of 2003 - Abdul Ghani Abu (Tanjong Malim, 2019)
The employment of the saviour concept in literature: Iraqi novelist production post-war of 2003 by Abdul Ghani Abu